Improving Anti-Corrosion Property of Aluminium Alloy by Fabrication MAO Coating via Mixing Titanium Potassium Oxalate into Electrolyte - Wei Song; Yasheng Xing; Zhen Song (Molecules)
Titanium potassium oxalate had been mixed into the electrolyte to improve the anti-corrosion property of the micro arc oxidation coating on the surface of the aluminium alloy. The surface and cross-section of the coating at different titanium potassium oxalate concentrations had been observed by scanning electron microscopy, showing that when the titanium potassium oxalate concentration was 10 g/L, the coating compactness was better. Additionally, the element content of the coating had been studied by the energy dispersive spectrometer, and results proved that the coating consisted of Al, O, Ti, Si, and P. The Ti increased with the increase in titanium potassium oxalate concentration. The X-ray diffractometer had been employed to analyze the crystalline structure of the coating. Then, it was found that after the micro arc oxidation, an alumina oxide coating was prepared on the surface of the aluminium alloy, and the Al2O3 and TiO2 characteristic peak was observed. Furthermore, the electrochemical workstation was used to test the anti-corrosion of the coating. It was proved that when the titanium potassium oxalate concentration was 10 g/L, the open circuit voltage, corrosion current, corrosion potential, and impedance of the coating were improved, and the anti-corrosion property of the aluminium alloy had been strengthened.